Kypriōn Politeia, the Political and Administrative Systems of the Classical Cypriot City-Kingdoms - Pestarino, Beatrice, (Mnemosyne, Supplements ;, 2022)
Through new readings and interpretation of Cypriot inscriptions - written in Cypriot-syllabic Greek, Eteocypriot, Phoenician, and alphabetic Greek - Kypriōn Politeia, the Political and Administrative Systems of the Classical Cypriot City-Kingdoms is the first book which reconstructs in detail the political and administrative systems of the Classical city-kingdoms of Cyprus. The book investigates the bodies of government beyond the Cypriot kings and the roles played by magistrates and officials in local governments, it analyses accounts of the headquarters of the main administrative and economic activities - such as palace archives, and tax collection hubs -, and demonstrates that these systems were similar in all the city-kingdoms.